Relationship between teachers' professional learning and teaching practices in Selangor, Malaysia - Roustaee, Roya (2015)
The main objective of this study is to investigate professional learning among teachers and its relationship with teachers’ classroom practices. The study is aimed to find the level of teachers' engagement in informal professional learning as well as the level of effective teaching practice based on constructivism approach. It also attempts to compare professional learning and teaching practices based on demographic variables such as gender, ethnicity, highest qualification and field of speciality. This study also seeks to determine the relationship between teachers’ years of experience with teachers'professional learning and teaching practices. The instrument was a questionnaire based on the work of Kwakman (2003) and Greer (1997). The questionnaires were administered to 500 secondary school teachers from 10 educational districts of Selangor. The findings indicated that the majority of teachers often engage in professional learning activities. In addition, the results indicated that teachers agree that they implement effective teaching practices according to constructivist teaching approach. One Way ANOVA test showed that Technical and Vocational teacher engaged significantly more in professional learning compared to teachers in other field of specialty. However there was no significant difference in teachers' professional learning based on gender, ethnicity, and teachers’ qualification. The results also indicated that Technical and Vocational teacher implement significantly more effective teaching practice based on constructivism approach compared to teachers in other fields of specialty. There was no significant difference in teaching practices based on gender, ethnicity and the teachers’ qualification. Pearson correlation test showed that teacher’s years of experience has a significant strong and positive relationship with professional learning and teaching practices. According to the main objective of this study, the data showed that there is a significant strong and positive relationship between teachers' professional learning and teaching practices. It can be concluded that when teacher engage more in informal professional learning, more effective teaching practice is implemented in the classroom. Based on the findings, it is recommended that school administrator need to encourage and support teachers to engage in professional learning. Incentive and support system should be provided to increase professional learning among teachers.